Three-Dimensional Application-Specific Protocol Architecture for Wireless Sensor Networks - Mostafa Baghouri; Abderrahmane Hajraoui; Saad Chakkor (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Many researchers assume that the distribution of the nodes is done in a two-dimensional environment in the reason that the height of this network is negligible compared to its width and length. However, in the reality, three-dimensional (3D) deployment of the wireless sensor networks is used. Therefore, many applications require 3D architecture such as underwater, space communications, atmospheric, forest or building. Unfortunately, the energy consumption and throughput in the 3D environment decreases considerably compared to 2D in which we can’t neglect them in some applications. In his paper we applied the 3D architecture in LEACH protocol and we prove by computer simulation how this 2D approximation is not reasonable since the lifetime of 3D WSN decrease by about 21% over than 2D WSN.